Night and evening shifts and risk of calling in sick within the next two days - a case-crossover study design based on day-to-day payroll data - Ann Dyreborg Larsen; Helena Breth Nielsen; Jonas Kirschheiner-Rasmussen; Johnni Hansen; Åse Marie Hansen; Henrik Albert Kolstad; Reiner Rugulies; Anne Helene Garde (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVE: Night and evening work is associated with risk of sickness absence, but little is known about the acute effects of these types of shifts on sickness absence. The aim of the current study is therefore to examine the risk of calling in sick within two days after a night or an evening shift. METHODS: By use of a case-crossover design, odds of calling in sick within two days after a night or an evening shift compared to day shifts were analyzed within the same person. Day-to-day information on shifts and sickness absence were derived from the Danish Working Hour Database on 44 767 cases. Data were analyzed using conditional logistic regression. The analyses were supplemented by extensive testing of methodological choices. RESULTS: Analyses showed higher odds of calling in sick after a night shift [odds ratio (OR) 1.22, 95% confidence intervak (CI) 1.14-1.30] and lower odds after an evening shift (OR 0.89, 95% CI 0.84-0.93) compared to day shifts within the same person. Testing of methodological choices suggested that in particular the duration of case and control periods, time between these periods along with the number of control periods affected the results. CONCLUSION: This large and unique within-person study among Danish hospital employees indicate that the risk of calling in sick is affected by the types of shifts, independently of sex, age, and time-invariant confounding. Extensive testing identified important methodological choices eg, length and number of included periods to consider when choosing the case-crossover design.